Caribbean Report 22-03-1993 - Rowe, Yvette (anchor); Bhola, Ronnie (correspondent); Musa, Said (interviewee); Martin, Lionel (correspondent); Perez, Maria (interviewee); Croskell, Hugh (correspondent); Richardson, Richie (interviewee); Douglas, Rosie (interviewee); Garner, Joel (interviewee) (The British Broadcasting Corporation, 1993)
Recent reports in two leading UK newspapers said that Britain plans to withdraw its military garrison from Belize, as part of the Ministry of Defense cost cutting exercise. Foreign Minister Said Musa said that the removal of the troops were a surprise to him, and this has raised much concern that the drug trafficking trade may increase and Belize may become a drug haven for traffickers as a result – correspondent Ronnie Bhola reports. The intercessional meeting of CARICOM leaders got on the way in Dominica, and host Dominican Prime Minster Eugenia Charles said that she was optimistic that this meeting would yield a positive outcome and firm decisions would be made on CARICOM issues - correspondent Yvette Rowe reports. Cuba has been forced to make a rare appeal for international help, due to the major battering experienced as a result of the hurricane waves and floods that hit the island. This has severely further weakened the country’s economy. The damages are estimated between 1.5 and 2 billion dollars, especially in the areas of tourism and agriculture (bananas and other staple export crops). Maria Perez - Cuban national and computer specialists in an interview with correspondent Lionel Martin pledges her volunteer assistance towards the crisis. The West Indies cricket team takes on Pakistan at Sabina Park in Jamaica as a series of three, 5 - One Day Internationals. The teams will also play 3 test matches in what is being billed as the unofficial World Championship. During last Summer’s tour of England, the Pakistani fast bowlers were accused in the press as using illegal methods to gain a prodigious late swing and some observers put it down to sour grapes. However, these allegations were never substantiated. In an interview with correspondent Hugh Croskell, former West Indies fast bowler - Joel Garner in defense of the Pakistanis said that the Pakistanis must be given credit for their hard work and development of their skills. Dominican Opposition Leader Rosie Bernard Douglas has stepped up his efforts to secure the future the port of Portsmouth, he recently met with Gordon Baker – Head of the West India Atlantic Department - Foreign and Commonwealth Office, to present his case that Portsmouth has been the first port since 1949 from which banners were exported since then and – correspondent Yvette Rowe reports from an interview with Mr. Douglas.
Headlines with anchor Yvette Rowe (00:00-00:36).
1. Recent reports in two leading UK newspapers said that Britain plans to withdraw its military garrison from Belize, as part of the Ministry of Defense cost cutting exercise (00:36-06:30).
2. The intercessional meeting of CARICOM leaders got on the way in Dominica. Host Dominican Prime Minster Eugenia Charles said that she was optimistic that this meeting would yield a positive outcome and firm decisions would be made on CARICOM issues (06:31-07:34).
3. Cuba has been forced to make a rare appeal for international help, due to the major battering experienced as a result of the hurricane waves and floods that hit the island (07:35-10:30).
Keywords: Drug traffic—Commerce--Belize.; United States-- Foreign relations--Belize.; Belize--Politics and government.; Caribbean Area-- Politics and government.; Caribbean Community—Commerce--Caribbean Area.; Hurricanes--Cuba.; Disaster relief--Cuba.; Cuba —Foreign Relations—United States.; Cuba-Politics and government.; Cricket—Tournaments--India.; Cricket—Tournaments-- West Indies.; Cricket captains--West Indies.; Cricket players -- India.; Cricket players --Caribbean Area.; Test matches (Cricket)-- India.; Harbors—History—Commerce--Dominica.; Harbors—History—Commerce--Caribbean Area.